Determinantes del nivel de morosidad de la caja municipal de ahorro y créditos de Maynas, periodo 2010 - 2019 - Del Castillo Ramírez, Luz del Pilar (2022)
This thesis seeks to study which are the determinants of credit default in the Municipal Savings and Credit Fund (MSCF) of Maynas, for the period 2010 - 2019. For this purpose, the approach of five explanatory variables will be used as potential determinants of delinquency in said microfinance entity, in this perspective an econometric linear regression model will be proposed that will allow establishing through individual significance tests (such as the student t test and the p-value test, considering a 95% level of confidence) which or which of these variables are determinants of the delinquency of the Maynas CMAC during the time horizon of analysis. In this way, it is possible to validate that only two of the proposed variables are determinants of delinquency, these variables are the growth of the national GDP of the services sector and the liquidity ratio of the Maynas MSCF. Given this, it is understandable to realize that only one of the determinants represents a control variable for the analysis microfinance entity, likewise the coefficient that is responsible for capturing what is the estimated percentage of effect caused by the liquidity ratio, it is equal to 0.0563958, so if the liquidity ratio were to increase by 1%, this is estimated to be associated with a 5.63958% rise in the level of delinquency.